Synoptic conditions accompanying the dry rainy season (2009/2010) in Iraq - Dr. Abbas Tarad Sajat. (Journal of College of Education, 2026)
The research discusses the frequency of rainy days in Iraq for the 2009/2010 season and analyzes the surface and upper atmospheric synoptic conditions associated with rainy days. Weather maps were analyzed for the pressure levels (1000) millibars and (500) millibars and for the observations (00) GMT and (12) GMT to analyze the frequency of pressure systems affecting the occurrence of rainy days in Iraq. By applying the dry year equation, it was observed that the number of stations experiencing a drought for the rainy season (2009/2010) reached (7), namely (Khanaqin, Baghdad, Al-Hay, Al-Diwaniyah, Najaf, Al-Nasiriyah, Basra), while the number of wet stations reached (3), namely (Mosul, Kirkuk, Al-Rutba). The largest decrease in the amount of rainfall was recorded at the Khanaqin station, which reached (75.8) ml, and at the Mosul station it reached (54.9) ml, and at the Al-Diwaniyah station it reached (50.0) ml, and at the Basra station it reached (48.7) ml, and at the Al-Nasiriyah station it reached (45.3) ml. The smallest decrease was recorded at the Al-Rutba station, which reached (11.8) mm. As for the general average decrease in the amount of rainfall, it reached (27.0) ml.